2023
DOI: 10.1021/acsnano.2c10039
|View full text |Cite
|
Sign up to set email alerts
|

Infected Diabetic Wound Regeneration Using Peptide-Modified Chiral Dressing to Target Revascularization

Abstract: Revascularization plays a critical role in the healing of diabetic wounds. Accumulation of advanced glycation end products (AGEs) and refractory multidrug resistant bacterial infection are the two major barriers to revascularization, directly leading to impaired healing of diabetic wounds. Here, an artfully designed chiral gel dressing is fabricated (named as HA-LM2-RMR), which consists of L-phenylalanine and cationic hexapeptide coassembled helical nanofibers cross-linked with hyaluronic acid via hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…It is well known that angiogenesis plays a key role in wound proliferation and remodeling by providing progenitor cells, oxygen and nutrients. 29 Enzyme-linked immunosorbent assay (ELISA) and immunofluorescence technologies were applied for monitoring the status of angiogenesis, respectively. It was found that the expression of VEGF was up-regulated in the CaPB NP-treated wound in comparison with that in the control group, and the level in the CaPB NP-treated group was increased by 2 times compared with that in the control group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that angiogenesis plays a key role in wound proliferation and remodeling by providing progenitor cells, oxygen and nutrients. 29 Enzyme-linked immunosorbent assay (ELISA) and immunofluorescence technologies were applied for monitoring the status of angiogenesis, respectively. It was found that the expression of VEGF was up-regulated in the CaPB NP-treated wound in comparison with that in the control group, and the level in the CaPB NP-treated group was increased by 2 times compared with that in the control group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the death of bacteria after hydrogel treatment was further verified by selecting the PNVBA-4 group with the highest bacterial survival rate as the target for laser confocal dead–live staining (Figure S3). The excellent antibacterial properties of the PNVBA hydrogels stem from their positively charged cations, which can attract negatively charged bacteria through electrostatic interactions, and combine with the cell membrane of the bacteria to destroy the integrity of the membrane. This results in the leakage of intracellular material and the inactivation of bacterial enzymes, eventually killing the bacteria .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Xing et al designed a chiral non-covalently crosslinked hydrogel dressing (HA-LM2-RMR) composed of l-phenylalanine and cationic hexapeptide co-assembled helical nanofibers cross-linked with hyaluronic acid via hydrogen bonding. 148 This hydrogel dressing contains abundant chiral and cationic sites that can selectively interact with the negatively charged microbial membrane. Notably, HA-LM2-RMR promotes angiogenesis of human umbilical vein endothelial cells by upregulating the expression of vascular endothelial growth factor (VEGF) and optic atrophy 1 (OPA1).…”
Section: Biomedical Applications Of Stimuli-responsive Peptide Hydrogelsmentioning
confidence: 99%